Functional disability and morbidities among the elderly people, according to socio-demographic conditions and indicative of depression - Bárbara Ferreira Agreli; Flavia Aparecida Dias; Pollyana Cristina dos Santos Ferreira; Nayara Cândida Gomes; Darlene Mara dos Santos Tavares (Universidad de Antioquia, 2017)
Objectives. To investigate the association of functional incapacity and the number of morbidities with sociodemographic, economic and health variables. Methods. This is a household survey, quantitative and transversal approach, conducted with 1,693 elderly in Uberaba-MG in 2012. We used the Mini-Mental State Examination, Katz Scale, Lawton and Brody Scale; Geriatric Depression Scale abbreviated and semi-structured instrument for evaluation of demographic data, economic and morbidities. Results. Functional incapacity in basic activities of daily living was associated with older age, a greater number of morbidities and presence of indicative of depression. Regarding the instrumental activities of daily living, functional incapacity was related to age, lower education and income, the greater number of morbidities and have indicative of depression. The largest number of comorbidities was associated with female sex, older age, lower income and indicative of depression. Conclusion. This study highlights the need for health actions directed to the oldest old, with less education and income, and indicative of depression to minimize the dependency on the performance of functional capacity and impact on morbidities.   How to cite this article: Agreli BF, Dias FA, Ferreira PCS, Gomes NC, Tavares DMS. Disability and morbidity among the elderly, according to sociodemographic conditions and indicative of depression. Invest. Educ. Enferm. 2017; 35(1):